Class Attendance System Using The Multiple Face Recognition Technique (Case Study: UPN - Budi Nugroho; Wahyu S.J. Saputra; Eva Yulia Puspaningrum (Nusantara Science and Technology Proceedings)
Currently, Face Recognition Technology has been widely implemented in various fields of life. One of them is to verify someone's identity. In this research, an application system has been developed related to the process of recording student attendance in a lecture class, where student attendance is obtained from faces data taken from image acquisition in a classroom. Automatically, face recognition results are inputed into the presence system. In this system, the lecturer can verify the results of the automatic attendance made by the system. This verification process is needed because the face recognition process carried out by the system cannot reach 100% accuracy. So, the student attendance record in class can be valid.